PENGENTASAN PERILAKU KONFORMITAS TEMAN SEBAYA: STUDI PENGARUH LAYANAN BK KLASIKAL DAN PENGUASAAN KONTEN - Hia, Restui; Lase, Famahato; Foera-era Lase, Justin; Rodearni Damanik, Hosianna (IKIP Siliwangi, 2025)
This study aims to examine the influence of classical guidance and content mastery services on reducing peer conformity behavior among students. Excessive conformity to peer pressure can hinder personal development and decision-making abilities. Therefore, intervention through guidance and counseling (GC) services is considered strategic in fostering student autonomy and resistance to social pressure. This associative quantitative research involved 15 Grade XI-AK students from SMK Negeri 1 Lahomi, selected through purposive sampling. Data were collected using a questionnaire and analyzed using partial regression (t-test) and simultaneous regression (F-test). The results show that both classical GC services (t = 3.310, p = 0.003) and content mastery services (t = 3.412, p = 0.004) have a significant partial effect on reducing peer conformity. Simultaneously, both variables also demonstrated a significant effect (F = 5.388, p = 0.021), with a coefficient of determination (R²) of 0.573, indicating that 57.3% of the variance in peer conformity behavior can be explained by the two services. These findings highlight the importance of structured GC services in promoting student independence, critical thinking, and resilience against negative peer influence.